Assessment of the prevalence of G6PD deficiency in RBCs of live new-borns born at tertiary care hospital - Garg, Surbhi; Joag, Girish G. (International Journal of Contemporary Pediatrics, 2019)
Background: Glucose-6-phosphate dehydrogenase is one of many enzymes that help the body process carbohydrates and turn them into energy. The mechanism by which G6PD deficiency causes neonatal hyper bilirubin may be due to hemolysis, but other mechanisms like secondary impairment of bilirubin conjugation and clearance by the liver may play a role. Therefore, through this study authors attempt to study the need for a newborn screening program for G6PD deficiency because of high prevalence and high risk of incidence due to consanguineous marriages in India. Methods: This study was a prospective cross-sectional study conducted among 350 consecutively born live new-borns in maternity wards and NICU of Krishna Institute of Medical Sciences and Hospital and Research Centre, Karad, Maharashtra during October 2016 to October 2017. Results: The maximum numbers of newborns were in the age group of 0-10 hours (36.80%), followed by in 11-20 hours (21.80%). The mean age among newborns was 2.86±5.83 hours. Out of 350 cases females were 181 (51.71%) and males (48.29%) and female to male ratio was 1.07:1. Conclusions: G6PD deficiency is one of the major causes of neonatal jaundice within 24 hours of life in new-borns. Hence, neonatal screening for G6PD deficiency could be an alternative to the haemolytic crisis prevention strategy in order to optimize affected young child care and prevention of crisis occurrence by avoiding taking contraindicated foods and drugs.